Hot-Casting Large-Grain Perovskite Film for Efficient Solar Cells: Film Formation and Device Performance - Liao, Kejun; Li, Chengbo; Xie, Lisha; Yuan, Yuan; Wang, Shurong; Cao, Zhiyuan; Ding, Liming; Hao, Feng (Nano-Micro Letters, 2020)
Organic–inorganic metal halide perovskite solar cells (PSCs) have recently been considered as one of the most competitive contenders to commercial silicon solar cells in the photovoltaic field. The deposition process of a perovskite film is one of the most critical factors affecting the quality of the film formation and the photovoltaic performance. A hot-casting technique has been widely implemented to deposit high-quality perovskite films with large grain size, uniform thickness, and preferred crystalline orientation. In this review, we first review the classical nucleation and crystal growth theory and discuss those factors affecting the hot-casted perovskite film formation. Meanwhile, the effects of the deposition parameters such as temperature, thermal annealing, precursor chemistry, and atmosphere on the preparation of high-quality perovskite films and high-efficiency PSC devices are comprehensively discussed. The excellent stability of hot-casted perovskite films and integration with scalable deposition technology are conducive to the commercialization of PSCs. Finally, some open questions and future perspectives on the maturity of this technology toward the upscaling deposition of perovskite film for related optoelectronic devices are presented. Highlights: 1 Recent advances of a hot-casting technique used to deposit high-quality perovskite films are reviewed. 2 Perovskite films with large grain size, uniform thickness, and preferred crystalline orientation are deposited. 3 Future perspectives on the upscaling of perovskite solar cell are described. <figure> <picture><source srcset="//media.springernature.com/lw685/springer-static/image/art%3A10.1007%2Fs40820-020-00494-2/MediaObjects/40820_2020_494_Figa_HTML.png?as=webp" type="image/webp"></picture> </figure>